Исследования Верхне-Салтовского археологического комплекса: проблемы и перспективы - Хоружая, М.В. (My University, 2012)
M. Khoryzha. The Investigation of the Archaeological Complex of Verkhniy Saltiv: the Problems And the Perspectives The work deals with the investigation of the views of the Soviet, Ukrainian and Russian researchers on the role and the destination of the archaeological complex of Verkhniy Saltiv. It has given the first component to the name of the Saltivo-Mayatskaya culture. The researchers suppose that Verkhniy Saltiv was: 1) the feudal palace which developed from the initial base station at the border of Khazaria and the Slavic population; 2) the city which was the tribal or military administrative centre of the northwestern Khazaria; 3) an ordinary checking point at the place of the Severskiy Donets crossing; 4) the status of the site can be determined only after the further research, and now there is no ground to consider it to be a “city” or a “palace”. There is no unanimous opinion about those against whom there was built a range of firmly reinforced Saltiv settlements along the southern border of the forest-steppe: 1) against the Slavic expansion from the North and the Northwest; 2) against the danger coming from the main territory of the Khazarian khaganate (from the east and the southeast). Besides there are some other questions concerning the archaeological site near Verkhniy Saltiv village which are to be solved immediately: 1) the determination of the time when the Saltiv settlement appeared; 2) the ethnic composition of the population dwelling there; 3) the relationship between the representatives of the catacomb burial rite and the population which left ground sepulchre in Netailovka; 4) the determination of the time when the settlement went out of existence and the reasons which lead to it; 5) the fortune of the Saltiv population after the settlement stopped existing. To solve all these questions we advise to use the analysis of the new research materials of the Verkhniy Saltiv catacomb and Netailovka ground necropolis.
Keywords: the Verkhniy Saltiv settlement; the Saltivo-Mayatskaya culture; the Severskiy Donets basin; the Alans; the Turkic Bulgarians